Studi Komparasi TGT Berbasis Media Kartu Soal dengan Team Quiz Berbasis Lelang Pertanyaan Terhadap Hasil Belajar IPA Siwa Kelas V MI Muhammadiyah Program Khusus Kartasura Tahun 2015/2016 - NURUL MUBAROKAH, WAHYU (2016)
This research is aiming at (1) differences the influence about the application of teams gams tournaments' strategies based question card and team quiz' strategies based question card and team quiz' strategies based question auctioned in learning outcome of natural sciences at the 5th grade students of MI Muhammadiyah Special Progam Kartasura 2015/2016 Academic Year, (2) the bigger influence in learning outcome of natural sciences between teams games tournaments' strategy based question card and teams quiz' strategy based question auctioned. This research is experimental research. The subject of of this reserch is all students at 5th grade of MI Muhammadiyah Special Program Kartasura 2015/2016 Academic Year. The technique of collecting data is test and documentation. The technique of analizing data is t-test which doing pre-requisite test like homogeneity test and normality test first. Based on the data analysis about 5 % degree' significance the result shows ttest - ttabel are 2,71 > 2,054 which the average of learning outcome at 5th grade A is bigger than 5th grade B, the result shows 87,778. The conclusion is (1) there are differences in learning outcome of natural sciences using teams games tournaments' strategy based question card and team quiz' strategy based question auctioned in learning outcome of natural sciences. (2) Teams games tournaments strategy based question card is bigger influence than team quiz' strategy based question auctioned in learning outcome of natural sciences.